Detergents, brothers-in-law and the MDPI journals - Aguillo, Isidro F. (Anuario ThinkEPI, 2021)
There is growing concern about the possible predatory nature of the MDPI editorial journals. The author identifies the practices of this publisher as pyramidal commercial techniques, which should be rejected in the field of scientific communication as they affect the selection and acceptance criteria of original works and generate a proliferation of monographs with questionable review processes. Although this publisher is not predatory, it is advised that authors do not edit or publish with it and that institutions cancel their agreements.